Literature Review on Economic and Ecological Comparisons of Alternative Drivetrain Technologies in Road Freight Transport - MEYER, Maeva; BOUSONVILLE, Thomas (Promet - Traffic&Transportation, 2026)
This literature review synthesises current academic research on alternative propulsion systems in road freight. Analysing over 150 scientific papers, it explores both economic and environmental dimensions. A structured bibliographic approach was employed, involving a three-phase selection process: evaluating the relevance of research platforms, identifying the most effective keyword combination and determining whether keyword searches in abstracts or full texts provide more pertinent results. A statistical evaluation highlights prevailing research trends and uncovers notable gaps, particularly in regional representation and vehicle type diversity, with a bias towards HDTs. Moreover, while the literature heavily emphasises electrification and hydrogen-based technologies, biofuels – despite their compatibility with existing internal combustion vehicles and their potential as a transitional fuel – remain underrepresented. Given their expected role in achieving EU climate objectives, further research is needed on the ecological, financial and operational impacts of their integration into freight networks. The review ultimately calls for more comprehensive investigations into infrastructure development and enhanced prospective analyses. Such research is critical for policymaking and for building stronger cooperation between shippers and carriers. In brief, given the transformative investments required for electric vehicle deployment, a deeper analysis of collaborative models could provide valuable strategies to accelerate the transition to zero-emission freight solutions.